2003
DOI: 10.1046/j.1365-2265.2003.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of two apolipoprotein A‐I gene MspI polymorphisms with high density lipoprotein (HDL)‐cholesterol levels and indices of obesity in selected healthy Chinese subjects and in patients with early‐onset type 2 diabetes

Abstract: The -75AA genotype was associated with higher HDL-cholesterol levels in the selected healthy, but not diabetic, subjects. The 83T allele was associated with greater indices of obesity in the diabetic patients, and with higher HDL-cholesterol in heterozygous healthy male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The evaluation of two or three risk variants revealed a significant influence of variants of the APOA1, CETP and SCARB1 genes on HDL-C levels. This finding is in agreement with studies of APOA1 and CETP genes in other populations 8,[33][34][35][36][37] . However, for the Gly2Ser SNP of the SCARB1 gene, the few studies conducted so far associated the presence of the 2Gly allele with a decrease in HDL-C levels.…”
Section: Discussionsupporting
confidence: 83%
“…The evaluation of two or three risk variants revealed a significant influence of variants of the APOA1, CETP and SCARB1 genes on HDL-C levels. This finding is in agreement with studies of APOA1 and CETP genes in other populations 8,[33][34][35][36][37] . However, for the Gly2Ser SNP of the SCARB1 gene, the few studies conducted so far associated the presence of the 2Gly allele with a decrease in HDL-C levels.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, it has been suggested that ?83T allele was also associated with higher transcription rate of APOA1, although ?83C/T polymorphism is located in the first intron [14]. Likewise, -75A and ?83T alleles have also been associated with higher HDL levels in some populations [13,14,19,20], whereas this association was not found in others [15,16]. Moreover, ?83T allele was associated with lower triglyceride levels in Chinese population [47].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, GT haplotype carriers presented decreased risk to develop obesity comparing to GC haplotype, suggesting that GT haplotype might be protective against obesity. In Chinese population, ?83T allele was associated with lower BMI in diabetic patients [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HDL metabolism is governed by lipoprotein lipase and hepatic lipase in such a way that lipoprotein lipase-mediated hydrolysis of triglyceride-rich lipoproteins enhances the incorporation of lipoprotein surface constituents to HDL [22, 25] and that hepatic lipase stimulates HDL triglyceride hydrolysis [25] and preβ-HDL generation [26]. Consequently, common genetic variations of these proteins involved in the metabolism of HDL may interact with one another, and may also affect the plasma HDL-C levels [27,28,29,30]. In individuals with M823 homozygotes, their HDL-C levels are supposed to be high.…”
Section: Discussionmentioning
confidence: 99%